Ethnographic Life: Method for an Ex Post Facto Anthropology - de Renó Machado, Igor José (Anthropologica, 2020)
Every ethnography has a beginning and an end, decided more or less arbitrarily by the anthropologist. In general, it has a simultaneously temporal and spatial beginning. Currently, spatial issues have been relaxed, but temporal issues are still a definite limit. This article reflects on the constitution of anthropological knowledge when the field has no such limits. What if any moment of our experiences can be seen a period of “ex post facto” ethnographic fieldwork? Is it possible to perform an ethnography without borders? What methods should we articulate to build knowledge without the separation between life and ethnography? Why is ethnography a life experience, when we do not often think of life as an ethnographic experience? And what happens if we think that life is indeed an ethnographic experience? This article deals with anthropological knowledge without borders and memory as a methodological resource.